Unruptured anterior communicating artery aneurysms presenting with seizure: Report of three cases and review of literature - Patil, Akshay (Medknow Publications & Media Pvt Ltd, 2013)
Aneurysms generally present with bleed and epileptogenic aneurysms are rare. Unruptured epilpetogenic anterior communicating artery aneurysms are extremely rare and anecdotal. We present three patients with unruptured anterior communicating artery aneurysms who presented with seizures and were surgically managed. Seizure might be related to the large size, presence of thrombus, microbleeds and surrounding gliosis. We suggest that large thrombosed anterior communicating artery aneurysms should be considered in the differential diagnosis of patients presenting with late onset of seizure and having a suprasellar lesion on imaging. Surgical clipping offers a fair chance of seizure freedom in selected patients.